Synergistic antibacterial photodynamic therapy of lysine-porphyrin conjugate and metal ions combination against Candida albicans and Mycobacterium tuberculosis - Wang, Xueming; Qin, Zhonghua; Wen, Ying; Chi, Mingxuan; Zhang, Lixia; Wu, Junping; Liu, Tianjun (Frontiers in Pharmacology, 2025)
IntroductionIn previous research, antibacterial photodynamic therapy using lysine-porphyrin conjugate LD4 effectively inactivated methicillin-resistant Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli; however, it exhibited limited activity against Candida albicans and Mycobacterium tuberculosis.MethodsTo address this limitation, we developed a synergistic antibacterial strategy by combining LD4 with Cu2+ or Zn2+.ResultsSynergy was confirmed via minimum inhibitory concentration and fractional inhibitory concentration index analyses, demonstrating 16- to 64-fold enhanced antibacterial efficacy compared to LD4 alone. Mechanistic studies revealed divergent pathways for LD4 + Cu2+ and LD4 + Zn2+: Zn2+ increased the reactive oxygen species yield and promoted LD4 uptake by pathogens, while LD4 + Cu2+ induced oxidative damage to cell walls and membranes in darkness, with light exposure exacerbating structural damage. Cytotoxicity assessments confirmed low toxicity, with >90% survival of normal cells at bactericidal concentrations. Fluorescence and infrared spectroscopy characterized metal-LD4 complexes, showing stabilization through interactions between amino and pyrrolic imino groups of LD4 and metal ions, which promoted non-radiative transitions and fluorescence quenching. Both combinations caused significant bacterial membrane disruption and growth suppression. Notably, cytotoxicity exhibited a biphasic dose-response linked to metal-LD4 complexation-dependent particle size changes.DiscussionThis study elucidated the enhanced antimicrobial mechanisms and safety of LD4-metal ion combinations. The findings resolve the limitations of LD4 while providing a theoretical framework for developing novel therapies against fungal and mycobacterial infections.